Regulation of BTB Dynamics in Spermatogenesis—Insights From the Adjudin Model. (9th August 2019) - Mao, Bai-Ping; Li, Linxi; Yan, Ming; Ge, Renshan; Lian, Qingquan; Cheng, C Yan
Abstract: During spermatogenesis, cell organelles, and germ cells, most notably haploid spermatids, are transported across the seminiferous epithelium so that fully developed spermatids line-up at the edge of the tubule lumen to undergo spermiation at stage VIII of the cycle. Studies have suggested that the microtubule (MT)-based cytoskeleton is necessary to support these cellular events. However, the regulatory molecule(s) and underlying mechanism(s) remain poorly understood. Herein, we sought to better understand this event by using an adjudin-based animal model. Adult rats were treated with adjudin at low-dose (10 mg/kg b.w.) which by itself had no notable effects on spermatogenesis. Rats were also treated with low-dose adjudin combined with overexpression of 2 endogenously produced blood-testis barrier (BTB) modifiers, namely rpS6 (ribosomal protein S6, the downstream signaling protein of mammalian target of rapamycin complex 1 [mTORC1]) and F5-peptide (a biological active peptide released from laminin-γ3 chain at the Sertoli-spermatid interface) versus the 2 BTB modifiers alone. Overexpression of these 2 BTB modifiers in the testis was shown to enhance delivery of adjudin to the testis, effectively inducing disruptive changes in MT cytoskeletons, causing truncation of MT conferred tracks that led to their collapse across the epithelium. The net result was massive germ cell exfoliation in the tubules, disrupting germ cell transport and cell adhesion across the seminiferous epithelium that led to aspermatogenesis. These changes were the result of disruptive spatial expression of several MT-based regulatory proteins. In summary, MT cytoskeleton supported by the network of MT regulatory proteins is crucial to maintain spermatogenesis.